Crystal structure of 4-(acetoxymethyl)-6-(3-acetyl-3-(4-fluorophenyl)thioureido)cyclohex-4-ene-1,2,3-triyl triacetate, C24H26FN2O9S - Liu Jin-Qiang; Ji Li (Zeitschrift für Kristallographie - New Crystal Structures, 2018)
C24H27FN2O9S, orthorhombic, P212121 (no. 19), a = 11.2301(12) Å, b = 11.9074(13) Å, c = 20.738(2) Å, V = 2773.1(5) Å3, Z = 4, Rgt(F) = 0.0389, wRref(F2) = 0.1022, T = 296(2) K.